The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-75390/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet-induced Obesity Leads to Behavioral Indicators of Pain Preceding Structural Joint Damage in Wild-Type Mice.

Abstract: Introduction: Obesity is one of the largest modifiable risk factors for the development of musculoskeletal diseases, including intervertebral disc (IVD) degeneration and back pain. Despite the clinical association, no studies have directly assessed whether diet-induced obesity accelerates IVD degeneration, back pain, or investigated the biological mediators underlying this association. In this study we examine the effects of chronic consumption of a high-fat or high-fat/high-sugar (western) diet on the IVD and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…One study evaluated pain behaviors and joint damage in the context of diet-induced obesity. This study reported obesity from a high-fat or Western diet (HFD) resulted in pain behaviors (increased mechanical sensitivity and altered spontaneous locomotion) in 24-week and 40-week old mice compared to 12-week old mice, and these behaviors preceded joint damage (61). Though the authors did not statistically report difference between age groups (only between different diet groups), if one looks at the chow-fed mice from 12-weeks to 40-weeks of age there is a decrease in spontaneous locomotion and increase in osteophytes in these aged mice, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated pain behaviors and joint damage in the context of diet-induced obesity. This study reported obesity from a high-fat or Western diet (HFD) resulted in pain behaviors (increased mechanical sensitivity and altered spontaneous locomotion) in 24-week and 40-week old mice compared to 12-week old mice, and these behaviors preceded joint damage (61). Though the authors did not statistically report difference between age groups (only between different diet groups), if one looks at the chow-fed mice from 12-weeks to 40-weeks of age there is a decrease in spontaneous locomotion and increase in osteophytes in these aged mice, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the disc do however align with the recent work of Gorth et al in hTNF-α overexpression mouse models and contribute to a growing body of evidence demonstrating the marginal impacts of systemic inflammation on overall disc health (30,61). Other in vivo models of systemic inflammation, including high fat diet-induced obesity, have shown disc architecture is not negatively impacted by inflammatory conditions that are not local (62,63). As seen in the structurally intact discs of these models, N153S NP tissues retained healthy, vacuolated cells expressing the NP-phenotypic marker CA3 and an aggrecan-rich matrix.…”
Section: Discussionmentioning
confidence: 96%